Creating an instrument to measure perceptions about access to health-related higher education programmes in South Africa - Orton, P.M.; Essack, S.; Nokes, K.M.; Brysiewicz, P. (South African Journal of Higher Education, 2020)
Background: The South African government has created countless policies that support the need to admit and graduate students who had been excluded from health-science programmes in higher education settings during the apartheid era. Objective: to develop a questionnaire that could be used by various stakeholders to obtain their perceptions about access to health sciences education in higher education settings. Method: A mixed methods design was used; the qualitative stage allowed for the identification of themes while the quantitative stage used measurement theory, to develop an instrument based on those themes. Results: The overarching theme was Achieving equity of access for success is multi-factorial and has diverse and complex challenges and eight sub-themes emerged which were used to create a 17-item questionnaire that has good content validity and reliability (Cronbach alpha=.767). Conclusion: Further psychometric testing with larger, more diverse samples will result in a refined instrument that can be administered to various stakeholder groups, such as current and potential health sciences students and faculties, and used in programme evaluation. Health science programmes can use the instrument to measure access within different disciplines and possible changes over time as innovations are piloted. Different health sciences programmes can be compared and contrasted and objective data can be used to make systematic organizational changes.